The Digital Competencies of the Workforce – A Priority of the National Program “Digital Bulgaria 2025” - Syarova, Elka (Research Papers, 2021)
The main goal of the present research is to analyze a certain set of problems and to identify opportunities to achieve the priority goal set in the National Program “Digital Bulgaria 2025” aimed at increasing digital competencies in its three main areas. In particular, the tasks are oriented in solving problems in the field of modernization of ICT education; improving the quality characteristics of the labor force in the context of ICT; increasing the number of highly qualified specialists in the field of ICT in Bulgaria. There is a comparison within peculiarities in the dynamics of a selected set of indicators in Bulgaria and the European Union (as a whole) in the period 2007 – 2019. It is concluded that there is good potential, which could be triggered to a large extent on the basis of implementation of a set measures in the forthcoming years. The research consists of various methods such as empirical descriptive and comparative analysis.
Keywords: Digital competencies and skills; Digital transformation; Labor force